Emicizumab prophylaxis in haemophilia patients older than 50 years with cardiovascular risk factors: Real‐world data. Issue 2 (17th February 2021) - Misgav, Mudi; Brutman‐Barazani, Tami; Budnik, Ivan; Avishai, Einat; Schapiro, Jonathan; Bashari, Dalia; Barg, Assaf A.; Lubetsky, Aaron; Livnat, Tami; Kenet, Gili
Abstract: Introduction: Emicizumab (Hemlibra™) is approved for prophylaxis of Haemophilia A (HA) patients with and without inhibitors. However, real‐world data on emicizumab use in the elderly HA patients with concomitant cardiovascular risk factors are lacking. Aim: To evaluate the safety and efficacy of emicizumab in a real‐world cohort of elderly HA patients. Methods: A prospective longitudinal observational study on HA patients over 50 years old treated, followed and monitored during emicizumab prophylaxis was conducted. We documented any bleeding or adverse events and collected plasma samples for emicizumab levels, aPTT and thrombin generation (TG). Results: Seventeen HA patients (2 with inhibitor), whose median age was 62.4 years (range: 51.5–77.1) composed the cohort, including 9/17 with multiple cardiovascular risk factors (high risk group). Seven patients had chronic HIV infection. The median follow‐up of our cohort was 400 days (range 89–805, IQR 211–479 days). The median annualized bleeding rate (ABR) significantly decreased for all patients. Among patients who displayed significant bleeding tendencies, emicizumab steady state levels as well as TG were lower as compared with the group. The ABR of four patients concomitantly treated by antiplatelet agents was significantly higher compared with the rest of the cohort. Neither thrombosis nor thrombotic microangiopathy (TMA) was encountered. Conclusions: Emicizumab prophylaxis for HA patients older than 50 years including those with cardiovascular risk factors was well tolerated. As lower emicizumab and TG levels were observed among bleeding patients, we suggest that monitoring laboratory assays could be of value within this age group.